Preparation of Dialdehydecellulose-3,5-dinitrobenzoate and Adsorption of Urea Nitrogen and Creatinine onto It - Jian, Li; Zu-Pei, Liang (Asian Journal of Chemistry, 2011)
Dialdehydecellulose-3,5-dinitrobenzoate (DAC-DNBZ) was prepared by esterification of 2,3- dialdehyde cellulose (DAC) and 3,5-dinitro benzoyl chloride (DNBC) in the lithium chloride/ N,N-dimethylacetamide (LiCl/DMA) solvent system and pyridine as catalyst. The effects of molar ratio of the materials, the amount of catalyst, reaction temperature and reaction time on the degree of substitution (DS) of dialdehydecellulose-3,5-dinitrobenzoate were investigated. The results suggest that dialdehydecellulose-3,5-dinitrobenzoate product was used as adsorbent for urea nitrogen and creatinine.